The lidar survey at Akraiphia (Boeotia): methodology and first results - Lucas, Thierry (Journal of Greek Archaeology, 2025)
In May 2021, a lidar survey was conducted in Boeotia by the French School at Athens. The aim was to collect lidar data from two sites investigated by the School since the nineteenth century: the sanctuary of the Valley of the Muses near Thespiai, and the urban center of Akraiphia. Both sites were surveyed in a single flight operated by Aerophoto.